Treatment of congenital dislocated hip by arthroplasty with femoral shortening - Keerati Chareancholvanich (2018)
This was a retrospective study of 15 hips in 11 patients with complete congenital dislocation of the hip treated by total hip arthroplasty and femoral shortening with a subtrochanteric double chevron derotation osteotomy. The mean age at the time of surgery was 51 years (range, 21-74 years), and the mean followup was 5.5 years (range, 2-8.5 years). Functional evaluation using the modified Harris hip rating system showed an excellent result in five hips and a good result in seven hips (80% success rate). The location of the hip center was lowered by a mean of 8.3 cm (range, 5.7-10.4 cm). Leg length discrepancy in seven patients with unilateral involvement was reduced from a mean of 3.9 cm (range, 1.7-8.2 cm) before surgery to a mean of 1.4 cm at the latest followup (range, 0-4 cm). The Trendelenburg sign was assessed in 10 of 15 hips and was corrected from a positive preoperative status to a negative postoperative status in eight of these 10 hips. There were no cases of nonunion, dislocation, nerve palsy, or radiographic loosening. The only complications were a supracondylar fracture below the femoral component in a patient with severe osteoporosis 6 months after surgery and loosening of the cemented titanium metal backed acetabular component in the same patient 1.5 years after surgery. The current series showed that total hip arthroplasty in combination with a subtrochanteric double chevron derotation osteotomy has promising short to midterm results in the treatment of complete congenital dislocation of the hip in adults.